100 años de la ciencia macromolecular: orígenes y perspectivas de futuro - Ayarza, Jorge (2021)
The year 2020 marked the 100th anniversary of the emergence of macromolecular science, also known as polymer science. In 1920, German chemist Herman Staudinger conducted pioneering research in which he coined the term ‘polymer’, giving rise to a new area of chemistry. Over many decades, a vast repertoire of polymeric materials and plastics were developed, with diverse applications in academic research, industry, transport, health, and electronics. Currently, this science still faces many challenges both at the fundamental research level as well as in engineering and technological applications. In this paper, we summarize the main historical events related to the development of macromolecular science, and also discuss current challenges and future perspectives.